Analysis of the Impact of Rights Issue Announcements on the Stock Returns of Companies Listed on the Indonesia Stock Exchange for the Period 2020-2023 - Pujiyasari, Winda; Sudarwadi, Hustianto; Simanjuntak, Verawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine whether there is a difference in the average stock return before and after the announcement of a rights issue in companies listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2023. The primary focus of this study is to examine the market reaction to corporate information in the form of new share issuance through the rights issue mechanism, as well as to assess the extent to which this event affects investors' perceptions of the company's performance. This study employs a quantitative approach, utilizing a parametric Paired Sample T-Test to examine the difference in average stock returns before and after the announcement of a rights issue. The research sample consists of 42 companies that conducted a rights issue during the 2020–2023 period. The observation period used was five days before and five days after the announcement of the rights issue. The results indicate a difference in average stock returns before and after the announcement of the rights issue; however, this difference is not statistically significant. This finding suggests that the market does not respond substantially to the announcement of a rights issue, indicating that a rights issue does not provide a strong signal to investors. This contradicts the prediction of signal theory, which expects a positive reaction from investors to corporate information. This study has implications for investors to be more cautious in evaluating corporate information, and for companies to enhance transparency and communicate the objectives of the rights issue strategically to form positive market perceptions.